EFFICACY OF SALICYLIC AND ASCORBIC ACIDS TO REDUCE THE EFFECT OF TRANSPORT STRESS ON LIVE WEIGHT, SOME BLOOD CHARACTERISTICS AND INTESTINAL VILLI OF BROILER CHICKENS - & et al., Al obaydy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This experiment was conducted and aimed to reducing mortality and losing the weight of birds transported to the slaughter house through reducing or Transport stress removal and thus to reduce financial losses. 150 birds used almost equal weights that were divided into three treatment groups and by five replicates for each treatment is control treatment (T1) without giving anything and treatment with salicylic acid concentration 1 g / liter of drinking water (T2) and treatment with ascorbic acid (T3) concentration 0.5 g / Liter of drinking water provided 24 hours before its transport. The transport process resulted in a highly significant decrease (P ≤ 0.01) in body weight in treatment T1 as it reached 4.66%, while it reached 1.68 and 1.09% in treatment T2 and T3, respectively. The transport process led to an increase in body temperature, H / L ratio, the concentration of glucose, aspartate transaminase (AST) and alanine transaminase (ALT) in the blood serum, as the transport process led to a very significant decrease (P ≤ 0.01) in the cholesterol concentration, Uric acid, intestinal villi length and crypts depth. T2 and T3 treatments showed their ability to reduce transport stress, especially T3, where they outperformed T1 in most traits. It is concluded from the study that adding ascorbic acid by 0.5 g / L drinking water 24 hours before transporting the chicks to the slaughter house reduces the transport stress and lessen financial losses, so it is recommended to use it.